População e território de forrageamento de uma colônia de Heterotermes tenuis (Hagen) (Isoptera, Rhinotermitidae) - Camargo-Dietrich, Célia Regina Rodrigues de [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Sociedade Brasileira de Zoologia, 2003)
Heterotermes tenuis (Hagen, 1858) is a subterranean termite that cause damage in forests, crops and urban areas. The population and foraging territory of an urban colony were determined using triple mark-release-recapture technique. Foraging population was estimated in 134,583 ± 5,803 individuals. The foraging territory encompassed an area of 175,5 m² and the maxim linear foraging distance was 36 m.
Population and foraging territory of a colony of Heterotermes tenuis (Hagen) (Isoptera, Rhinotermitidae)
Keywords: Isoptera; Rhinotermitidae; Heterotermes tenuis; population; territory